The impact of Additive Manufacturing Adoption on Supply Chain Complexity and Uncertainty: A Literature review - Nguyen, Thuy Dung (2017)
Purpose: This dissertation aims to conduct an overview research regarding the topic of Additive Manufacturing adoption along with the identification of impacts of such adoption to the supply chain complexity and uncertainty. Throughout the dissertation, the areas of interests and research trend have been investigated while also identified the gaps within the pool of literature to provide recommendations for future directions of AM adoption research.